DJOK MENTAYA'S BIOGRAPHIC VALUE (1939-1994) AS A SOURCE OF LEARNING IPS - M Riski Syahbandi Syahbandi (Universitas Lambung Mangkurat, 2022)
Huzai Junus Djok Mentaya is a press figure in South Kalimantan. He started his career as an Editor at the Student's pulpit, the campus newspaper as the mouthpiece for WE at Lambung Mangkurat University in the 1960s. And he was active in the student/Tritura movement in South Kalimantan to overthrow the Old Order and the PKI in 1966 and was a member of 66 activists. Until he founded the largest print media in Banjarmasin, namely the Banjarmasin Post which was founded on August 2, 1971. With his determination and hard work, the press continued to progress and develop. fast. The end result of his struggle, Djok Mentaya, has his name enshrined on a street in Banjarmasin, to commemorate and honor his services. This study explains the biography and describes the value of Djok Mentaya as a press figure in South Kalimantan. And describes efforts to make values as a source of social studies learning.This study uses historical and descriptive qualitative research methods.The results of the study show that the figure of Djok Mentaya has a value ofcourage, unyielding and willing to sacrifice, hard work, so that later it is used as a social studies learning resource and integrated into the social studies learning process.